Effect of Various Duct Shapes and Blade Sections on the Efficiency Performance of Horizontal Axis Tidal Current Turbine - Gandomani Mahdi Azimi; Ghassemi Hassan; He Guanghua (Polish Maritime Research)
This research emphasizes the importance of optimal design for tidal turbines under various ducts and blade sections to enhance efficiency. A Reynolds-Averaged Navier-Stokes (RANS) solver with turbulence model is used to investigate the performance of horizontal-axis tidal current turbines (HATCT) under different ducts and blade sections. Analyses were conducted using various meshes and, in several stages, to ensure the accuracy of the results. Six types of different blades sections and winglets are selected and the numerical results of thrust, torque and power coefficients are compared. demonstrating the accepTable accuracy of this analytical method. It is indicated that the effect of the winglet caused to increase the power coefficient. The numerical results were compared and validated with experimental data and found in good agreement. Finally, the effect of the different duct shapes with turbine type 1 at TSR = 5 is obtained with significant results of the power coefficient.